Future of Journal of Medical and Psychological Trauma: Tips for the Authors and Editors - Mohammed Al-breiki (Journal of Medical and Psychological Trauma, 2018)
An editorial outlines aims for the journal and offers practical tips to authors and editors on study design, reporting, and ethics in trauma research.